Radium‐223 plus Enzalutamide Versus Enzalutamide in Metastatic Castration‐Refractory Prostate Cancer: Final Safety and Efficacy Results. (23rd September 2021) - Maughan, Benjamin L.; Kessel, Adam; McFarland, Taylor Ryan; Sayegh, Nicolas; Nussenzveig, Roberto; Hahn, Andrew W.; Hoffman, John M.; Morton, Kathyrn; Sirohi, Deepika; Kohli, Manish; Swami, Umang; Boucher, Kenneth; et al.
Abstract: Lessons Learned: Long‐term safety of radium‐223 with enzalutamide was confirmed in this clinical trial. PSA‐PFS2 was prolonged with the combination compared with enzalutamide alone. Background: Previously, we showed the combination of radium‐223 and enzalutamide to be safe and associated with improved efficacy based on a concomitant decline in serum bone metabolism markers compared with enzalutamide alone in a phase II trial of men with metastatic castration‐resistant prostate cancer (mCRPC) [1]. Methods: Secondary endpoints were not included in our initial report, and we include them herein, after a median follow‐up of 22 months. These objectives included long‐term safety, prostate‐specific antigen (PSA)–progression‐free survival (PFS), and radiographic progression‐free survival; PSA‐PFS2 (time from start of protocol therapy to PSA progression on subsequent therapy); time to next therapy (TTNT); and overall survival (OS). Survival analysis and log‐rank tests were performed using the R statistical package v.4.0.2 (https://www.r-project.org ). Statistical significance was defined as p  < .05. Results: Of 47 patients (median age, 68 years), 35 received the combination and 12 enzalutamide alone. After a median follow‐up of 22 months, final safety results did not show any increase in fractures or other adverse events in the combination arm. PSA‐PFS2 was significantly improved, and other efficacy parameters were numerically improved in the combination over the enzalutamide arm. Conclusion: The combination of enzalutamide and radium‐223 was found to be safe and associated with promising efficacy in men with mCRPC. These hypothesis‐generating results portend well for the ongoing phase III PEACE III trial in this setting.